Analysis of LpA levels in young patients after ACS: getting to know less famous risk factors. (14th October 2021) - Luna, M; Rodriguez Cordoba, A; Rodriguez Capitan, J; Martinez Carmona, J D; Diaz Exposito, A; Marquez Camas, P; Garcia Rodriguez, L; Palma Marti, L; Angullo Gomez, M; Doncel Abad, M V; Berteli Garcia, G; Mendez Natera, R; et al.
Abstract: Introduction: Lipoprotein A (LpA) has been shown to be an emerging risk factor, proposing that values greater than 60 mg/dl increases cardiovascular risk. There are few data about LpA values in young patients who have suffered a major cardiovascular event. Purpose: The objective of this work was to describe the LpA values observed in young patients admitted for acute coronary syndrome in our center, and subsequently to compare these values according to the patients' previous cardiovascular risk. Methods: This is a descriptive and observational study, in which all male patients under 65 years and women under 70 years who have suffered STEMI or NSTEMI from November 2019 to February 2021 admitted to our center were consecutively included. In addition to LpA values, the following variables were recollected: age, sex, high blood pressure, diabetes mellitus, dyslipidemia, stroke, chronic kidney injury, smoking, alcoholism, toxics, total cholesterol and SCORE risk. Results: 159 patients were included. The mean of LpA value was 41, 08 mg/dl (standard deviation 38, range 1–155, percentile 25th: 9, 7; percentile 50th: 28, 8; percentile 75th: 59, 1). 24, 5% presented levels of LpA greater than 60 mg/dl. The percentage of patients with LpA levels >60 mg was 32, 4% in low SCORE group and 22, 4% in greater than low SCORE group without significant differences. The table compares the LpA values according to the cardiovascular risk SCORE those patients presented before the acute coronary syndrome (low SCORE vs moderate, high or very high SCORE). As we can see in the table, we found a trend to present higher LpA values in patients with low SCORE risk compared to those with higher than low SCORE risk, without reaching statistical significance. Conclusions: In a sample of young patients with acute coronary syndrome, the LpA mean was 41, 08 mg/dl. 24, 5% of patients had values of LpA greater than 60 mg/dl. No significant differences were found according to the SCORE prior to the event, although there was a non-significant trend towards a higher LpA in patients with low SCORE. Funding Acknowledgement: Type of funding sources: None.